Penerapan Knowledge Sharing Untuk Peningkatan Layanan Perpustakaan Perguruan Tinggi - Safitri, Dyah (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2014)
Sharing knowledge is one of important elements in academic libraries. The activity uses ICT to inform one another. Most academic libraries in Indonesia, supporting infrastructures and reward are the main factor to conduct the activity. The implementation of such activity, especially in academic libraries, has resulted some beneficial both for librarians and its users. Motivation is considered as one of important aspects in sharing knowledge. By having supporting facilities or infrastructures, the activity can run smoothly and properly.